Concurrent enhancement in the H2 and UV sensing properties of ZnO nanostructures through discontinuous lattice coating of La3+via partial p–n junction formation. Issue 9 (19th February 2018) - Kathiravan, Deepa; Huang, Bohr-Ran
Abstract : A discontinuous lanthanum (La 3+ )-coated ZnO nanorod-based multisensor was fabricated for the first time. The H2 gas and UV sensing properties were studied simultaneously. Abstract : The development of multifunctional sensors with surface-modified one-dimensional ZnO nanostructures has attracted significant scientific interest due to their versatility. Herein, we present a simple hydrothermal route to coat lanthanum (La 3+ ) ions onto the surface lattice of ZnO nanorods (La-coated ZNRs). The as-prepared ZnO nanorods (ZNRs) without La 3+ ion coating were also synthesized under the same conditions for comparison. Each sample was then fabricated as a multisensor with interdigitated electrodes, and their H2 gas and UV sensing properties were systematically studied. Thus, the La-coated ZNR-based multisensor exhibited remarkable H2 sensing and efficient UV detection properties when compared to that of the as-prepared ZNRs. An ultra-high H2 response of 63.8% was achieved even at a low detection level (ppm) with an ultra-fast response (15 s) and recovery time (9 s). Also, excellent UV sensing properties were observed with a high switch ratio ( I photo / I dark ) of 256.3. Moreover, the present multisensor was also revealed to exhibit superb sensitivity, stability, repeatability and selectivity towards H2 gas and UV light. This outstanding enhancement in the multisensing measurements of La-coated ZNR-based multisensors can be ascribed to their high oxygen vacancies, and the formation of partial p–n junctions on their discontinuous surface lattices. Furthermore, this sensor was also utilized for the simultaneous detection of UV light and H2 gas in a single measurement. The prominent feature of the incorporation of La 3+ ions into ZNRs is the improvement in efficient multisensors, but, in addition, this combination can be highly useful for H2 storage materials.